Factors affecting posaconazole plasma concentrations: a meta-analysis and systematic review - Qu, Ruochen; Liu, Yan; Zhao, Yan; Wang, Ziyi; Yuan, Shizhao; Liu, Shuai; Yu, Jing (Frontiers in Pharmacology, 2024)
BackgroundPosaconazole is a potent antifungal agent widely used to manage invasive fungal infections, especially in immunocompromised individuals. Achieving optimal therapeutic concentrations of posaconazole can be challenging due to interpatient variability, the availability of multiple formulations, and various dosing strategies.MethodsWe conducted a systematic search of PubMed, EMBASE, and the Cochrane Library to identify studies evaluating factors that influence blood concentrations of posaconazole. The primary outcome was the assessment of posaconazole concentrations in relation to various influencing factors, including age, sex, drug interactions, disease state, administered dose, and formulation.ResultsOur analysis included 46 studies involving a total of 8,505 patients. Co-administration of drugs that affect posaconazole metabolism significantly reduced its concentrations. High-fat meals, age, and sex did not have a significant impact on posaconazole oral suspension (POS) concentrations. Diarrhea substantially decreased concentrations of both delayed-release tablets (DRT) and POS. Neither vomiting nor mucositis significantly affected POS concentrations. Acid-suppressing agents, such as H2 receptor antagonists and proton pump inhibitors, notably decreased POS concentrations but had no significant effect on DRT. Comparative studies of different dosage forms revealed significantly higher concentrations with DRT compared to POS.ConclusionDRT maintain more stable concentrations than POS and are not affected by acid-suppressing drugs. Given the significant fluctuations in posaconazole concentrations, patients experiencing diarrhea require close monitoring.Systematic Review RegistrationPROSPERO, Identifier CRD42023428822 (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023428822).